2010
DOI: 10.1163/138577210x12634696333550
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Properties of New Fluorinated Poly(imide siloxane) Co-polymers from 4,4′-(Hexafluoro-isopropylidene)diphthalic Anhydride

Abstract: Several new poly(imide siloxane)s co-polymers have been prepared by the reaction of 4,4 -(hexafluoroisopropylidene)diphthalic anhydride (6FDA) with commercially available 4,4 -oxydianiline (ODA) and with five different novel trifluoromethyl-substituted diamines, each with 20 wt% aminopropyl-terminated polydimethylsiloxane (APPS). The poly(imide siloxane)s are well characterized by different spectroscopic, thermal, mechanical and electrical techniques. The synthesized polymers exhibit good solubility in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…There are several reports on random fluorinated copoly(imide siloxane)s so far. [258][259][260][261][262][263][264] The exceptionally high solubility of the poly(imide siloxane)s could be ascribed to the presence of flexible aminopropyl linkages in the polymer backbone which imparts ease of penetration of solvent molecules in between the polymer chains and the presence of bulky -CF 3 groups reduces the chain packing density and hence enhances the solubility to a great extent. Thermal stability showed a decrease for the siloxane containing polymers compared to the respective homopolymers without siloxane units because of the weak aminopropyl linkages present in the polymer backbone.…”
Section: 211mentioning
confidence: 99%
“…There are several reports on random fluorinated copoly(imide siloxane)s so far. [258][259][260][261][262][263][264] The exceptionally high solubility of the poly(imide siloxane)s could be ascribed to the presence of flexible aminopropyl linkages in the polymer backbone which imparts ease of penetration of solvent molecules in between the polymer chains and the presence of bulky -CF 3 groups reduces the chain packing density and hence enhances the solubility to a great extent. Thermal stability showed a decrease for the siloxane containing polymers compared to the respective homopolymers without siloxane units because of the weak aminopropyl linkages present in the polymer backbone.…”
Section: 211mentioning
confidence: 99%
“…Most SIPEs enable batteries to perform only at elevated temperatures with relatively low charge-discharge rates. [33][34][35] Based on this idea, we developed a methodology to synthesize a polysiloxane based single ion conducting gel polymer electrolyte with grafted bis(sulfonyl) imide groups via a hydrosilylation process. [30,31] It has been well demonstrated that ion migration occurs predominantly in amorphous opulent phase where transport properties, such as ionic conductivity, diffusivity and mechanical relaxation, are explicitly related to the segmental movement of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…31 Unlike most of the polymers used as electrolytes, polysiloxanes, which are inherently amorphous in nature and possess very low T g with high thermal stability and good mechanical strength, may potentially serve as useful backbone polymers for designing SIPEs. [33][34][35] Based on this idea, we developed a methodology to synthesize a polysiloxane based single ion conducting gel polymer electrolyte with graed bis(sulfonyl) imide groups via a hydrosilylation process. Hydrosilylation is a catalyst assisted technique of adding Si-H bonds across unsaturated bonds.…”
Section: Introductionmentioning
confidence: 99%
“…All copolymers displayed two T g values, one around -100 °C and the other in 129-184 °C range depending on the chemical structure and composition of the copolymers. All samples displayed excellent tensile properties withA c c e p t e d M a n u s c r i p t ultimate tensile strengths in 26 to 33 MPa range and elongation at break values of 120-130%(205, 206).PDMS-imide segmented and graft copolymers containing fluorinated imide hard segmentswere also investigated(198)(199)(200)(201)(202)(203)(204)(207)(208)(209)(210).Copolymers were prepared from aminopropyl terminated PDMS oligomers with <M n > values 900, 1,680 and 4,600 g/mol(203,211,212). High molecular weight copolymersobtained displayed microphase separated morphologies based on the DSC studies and good thermal stability.…”
mentioning
confidence: 99%